Efficient Identity-Based Broadcast Encryption Scheme on Lattices for the Internet of Things. (13th December 2021) - He, Kai; Liu, Xueqiao; Liu, Jia-Nan; Liu, Wei
Abstract : In an identity-based broadcast encryption (IBBE) scheme, the ciphertext is usually appended with a set of user identities to specify intended recipients. However, as IBBE is adopted in extensive industries, the demand of anonymity for specific scenarios such as military applications is urgent and ought no more to be ignored. On the contrary, how to optimize computation and communication is an unavoidable challenge in the IBBE scheme construction, especially in the large-scaled resource-limited wireless networks such as the Internet of Things (IoT), where the cost of computation and communication should be mitigated as much as possible since other functions including connectivity and privacy should be given the top priority. Thus, we present an IBBE scheme from the lattice, in which we employ the Chinese remainder theorem and lattice basis delegation in fixed dimensions to obtain several desirable characteristics, such as constant-size public parameter, private key, and ciphertext. In addition, our encryption and decryption algorithms are more efficient than broadcast encryption (BE) schemes based on number-theoretic problems. To be noticed, our scheme can simultaneously achieve confidentiality and outsider anonymity against the chosen-plaintext attack under the hardness of the learning with error (LWE) problem.